Integrated approach to knowledge management initiatives programme : towards designing an effective knowledge management system / Juhana Salim, Masnizah Mohd and Mohd. Shahizan Othman - Salim, Juhana; Mohd, Masnizah; Othman, Mohd. Shahizan (Faculty of Information Management, 2011)
There have been varied opinions about the approaches, methods and implementation of knowledge management initiatives. The varied approaches can be integrated to ensure that the right knowledge can be created, captured, stored, and disseminated. In addition, managing both explicit and tacit knowledge will enable knowledge in individuals to be transferred and shared for new knowledge to be created, further expanded and embodying it quickly in new products and services, technologies and systems. One of the perspectives on knowledge management which is given much emphasis is the Japanese perspectives that focuses on cultural behavioural approach. This paper explains how the theory of knowledge conversion can be an influential element in knowledge management initiatives programmes. Another area that requires much attention is the tool and enabler that includes the application of technology and resources to enhance content intelligence to expedite access and reuse of the knowledge captured and stored. On the contrary, this paper highlighted on the issue whether access itself will have a substantial impact on business performance especially as mountains of new information are placed online. To address such issue, organizations need to consider the systematic approach that do not merely focus on process and technology. Thus, the cultural behavioural aspect of knowledge management discussed in great length is integrated into the knowledge management system architecture which is designed, based on the fact that knowledge management relies heavily on human intellectual effort and skills.